Healthy Minds in the Twentieth Century In and Beyond the Asylum - Taylor, Steven J.; Brumby, Alice (Mental Health in Historical Perspective,, 2020)
This open access edited collection contributes a new dimension to the study of mental health and psychiatry in the twentieth century. It takes the present literature beyond the 'asylum and after' paradigm to explore the multitude of spaces that have been permeated by concerns about mental well-being and illness. The chapters in this volume consciously attempt to break down institutional walls and consider mental health through the lenses of institutions, policy, nomenclature, art, lived experience, and popular culture. The book adopts an international scope covering the historical experiences of Britain, Ireland, and North America.In accordance with this broad approach, contributions to the volume span academic fields such as history, arts, literary studies, sociology, and psychology, mirroring the diversity of the subject matter. This book is available open access under a CC BY 4.0 license at link.springer.com.